Mobilisasi Massa Melalui Tajen Dalam Pemilihan Umum Legislatif Tahun 2014 Di Kabupaten Tabanan - Eggy Segel, I Kadek; Azhar, Muh.Ali; Noak, Piers Andreas (Jurnal Nawala Politika, 2017)
ABSTRACT        Tajen is a form of gambling in Bali, and is a social pathology that can destructive people’s live. However, the tajen remains a popular and become a political commodity. The current era of decentralization, created political elites in regions with social capital owned, compete and mobilize all of social capital in society for power and resources in the region through legislative elections. Mobilization through the existing tajen groups in Tabanan carried out by local political elites to win on the legislative elections in 2014. The purpose of this research was to determine, how the tajen as a social pathology was used to mobilize the masses in the 2014 Legislative Election at Tabanan Regency. The research used qualitative method with descriptive research type of analysis. Primary data was collected through interview technique purposive sampling and snowball sampling, and secondary data obtained from news, articles on internet and related books of the research. This research uses Putnam's social capital theory. The results of this research indicate ; First, mass mobilization by the legislative candidate through sekaa tajen in the electoral area of Tabanan 2, conducted by directed families of sekaa tajen, and directed the people of the village that becomes the arena of tajen, to choose candidate that carried by the sekaa tajen. This is due to social capital and high socio-economic status of legislative candidate, legislative candidate promises the protection to the sekaa tajen, in order that tajen to safe. second, There is a public dilemma of tajen, where in one side the tajen is considered as a culture that has been passed down from generation to generation, and on the other hand according to law KUHP article 303 Tajen is a criminal offense. Keywords : Tajen, Mass Mobilization, Local Political Elite, Social Capital, Decentralization